Default mode network alterations underlie auditory verbal hallucinations in schizophrenia. (November 2022) - Marino, Marco; Spironelli, Chiara; Mantini, Dante; Craven, Alexander R.; Ersland, Lars; Angrilli, Alessandro; Hugdahl, Kenneth
Abstract: Although alterations of the default mode network (DMN) in schizophrenia (SZ) have been largely investigated, less research has been carried out on DMN alterations in different sub-phenotypes of this disorder. The aim of this pilot study was to compare DMN features among SZ patients with and without auditory verbal hallucinations (AVH). Three groups of 17 participants each were considered: patients with hallucinations (AVH-SZ), patients without hallucinations (nAVH-SZ) and age-matched healthy controls (HC). The DMN spatial pattern was similar between the nAVH-SZ and HC, but the comparison between these two groups and the AVH-SZ group revealed alterations in the left Angular Gyrus (lAG) node of the DMN. Using a novel approach based on normalized fractional Amplitude of Low-Frequency Fluctuations (fALFF), the AVH-SZ subgroup showed altered spectral activity in the DMN compared with the other two groups, especially in the lower-frequency bands (0.017–0.04 Hz). Significant positive correlations were found for both SZ groups collapsed, and for the nAVH-SZ group alone between delusional scores (PANSS-P1) and slow fALFF bands of the DMN. Narrowing the analysis to the ROI centered on the lAG, significant correlations were found in the AVH-SZ group for hallucination scores (PANSS-P3) and Slow-5 and Slow-4 (both positive), and Slow-3 (negative) fALFF bands. Our results reveal the central role of the lAG in relation to hallucinations, an important cortical area connecting auditory cortex with several hubs (including frontal linguistic centers) and involved in auditory process monitoring. Highlights: Schizophrenia (SZ) patients might experience auditory verbal hallucinations (AVH). Default Mode Network (DMN) is unaltered for SZ patients, but not in presence of AVH. Alterations in DMN might be linked to the presence of AVH in SZ patients. Left Angular Gyrus (lAG) might play a key role in the generation of AVH. Fluctuations derived from DMN and lAG correlates with the severity of hallucinations.